Integrasi Pendidikan Berbasis Gender Dengan Ilmu Islam (Studi Kasus di MI Miftahul Akhlaqiyah Bringin Semarang) - Luq Yana Chaerunnisa (eL Bidayah: Journal of Islamic Elementary Education, 2023)
This study aims to determine the teacher's role in the implementation of gender-based integration of basic education with Islamic science. Understanding The integration of gender-based education with Islamic knowledge will affect the development and formation of the mindset and personality of children in adulthood, as well as efforts to minimize acts of sexual violence and gender inequality. This study uses a descriptive qualitative study. With data collection techniques through documentation, namely interviews, data collection from articles, web, books and so on. The research subjects were the principal, educator at MI Miftahul Akhlaqiyah Bringin Semarang. The results of the study indicate that the implementation of the integration of gender-based basic education with Islamic knowledge is carried out through habituation, example, and the absence of discriminatory attitudes by educators in the learning process. In addition, there are no special materials or themes regarding gender studies in the lesson plans, because gender values have been integrated with Islamic science in the learning process. [Penelitian ini bertujuan untuk mengetahui peran guru terhadap pelaksanaan integrasi pendidikan dasar yang berbasis gender dengan ilmu islam. Pemahaman Integrasi pendidikan berbasis gender dengan ilmu Islam akan mempengaruhi perkembangan dan pembentukan pola pikir dan kepribadian anak di masa dewasa, sekaligus upaya untuk meminimalisir adanya tindak kekerasan seksual dan ketidaksetaraan gender. Penelitian ini menggunakan studi kualitatif deskriptif. Dengan teknik pengumpulan data melalui dokumentasi, yakni wawancara, pengumpulan data dari artikel, web, buku dan lain sebagainya. Subjek penelitian ialah pendidik di MI Miftahul Akhlaqiyah Bringin Semarang. Hasil dari penelitian menunjukkan bahwa pelaksanaan integrasi pendidikan dasar berbasis gender dengan ilmu islam dilakukan melalui pembiasaan, keteladanan, serta tidak adanya sikap diskrirminatif oleh pendidik dalam proses pembelajaran. Tidak ada materi ataupun tema khusus mengenai kajian gender dalam RPP, karena nilai-nilai gender telah diintegrasikan dengan ilmu islam dalam proses pembelajaran]